Preoperative detection of sentinel lymph nodes with hybrid SPECT/computed tomography imaging may improve the accuracy of sentinel lymph node biopsies in patients with early stages of cancer of the oesophagus or gastro-oesophageal junction. Issue 11 (November 2020) - Gabrielson, Stefan; Tsai, Jon A.; Celebioglu, Fuat; Nilsson, Magnus; Rouvelas, Ioannis; Lindblad, Mats; Bjäreback, Annie; Tomson, Artur; Axelsson, Rimma
Abstract : Objectives: The aim of this study was to investigate the sentinel lymph node biopsy (SLNB) method in patients with cancer of the oesophagus or gastro-oesophageal junction (GOJ) guided by preoperative hybrid single-photon emission tomography/computed tomography (SPECT/CT) lymphoscintigraphy. Methods: Thirty-nine patients with stage T1–T3, any N-stage, M0 cancer of the oesophagus or GOJ planned for curatively intended esophagectomy underwent preoperative SPECT/CT lymphoscintigraphy following endoscopically guided submucosal injection of radiocolloid and intraoperative radio-guided SLNB using a hand-held gamma scintillation device. Results: The detection rate in preoperative SPECT/CT imaging was 88%. The median number of detected SLN stations in preoperative imaging was 1 (range 0–4). At least one suspected SLN was identified in all intraoperative SLNP procedures. In six cases, no lymph nodes were identified in the SLNB. In six cases, the SLNB was false negative. The sensitivity for successful SLNB procedures was 20%, the specificity was 100% and the accuracy was 75%. Conclusions: Preoperative SLN mapping using SPECT/CT yields a high number of detected SLN stations compared to previous studies using planar imaging. The accuracy of the SLNB method in patients with predominantly ≥T3-stage tumours and with a history of previous neoadjuvant treatment is poor, and the method is not recommended in these patient groups.